Origin of fungal biomass degrading enzymes: Evolution, diversity and function of enzymes of early lineage fungi. Issue 1 (January 2019) - Lange, Lene; Pilgaard, Bo; Herbst, Florian-Alexander; Busk, Peter Kamp; Gleason, Frank; Pedersen, Anders Gorm
Abstract: The aim of this study was to elucidate the evolution of enzyme secretome of early lineage fungi to contribute to resolving the basal part of Fungal Kingdom and pave the way for industrial evaluation of their unique enzymes. By combining results of advanced sequence analysis with secretome mass spectrometry and phylogenetic trees, we provide evidence for that plant cell wall degrading enzymes of higher fungi share a common ancestor with enzymes from aerobic ancient fungi. Sequence analysis (HotPep, confirmed by dbCAN-HMM models) enabled prediction of enzyme function directly from sequence. For the first time, oxidative enzymes are described here in early lineage fungi (Chytridiomycota & Cryptomycota), which supports the conceptually new understanding that fungal LPMOs were also present in the early evolution of the Fungal Kingdom. Phylogenetic analysis of fungal AA9 proteins suggests an LPMO-common-ancestor with Ascomycetes and Basidiomycetes and describes a new clade of AA9s. We identified two very strong biomass degraders, Rhizophlyctis rosea (soil-inhabiting) and Neocallimastix californiae (rumen), with a rich spectrum of cellulolytic, xylanolytic and pectinolytic enzymes, characteristically including several different enzymes with the same function. Their secretome composition suggests horizontal gene transfer was involved in transition to terrestrial and rumen habitats. Methods developed for recombinant production and protein characterization of enzymes from zoosporic fungi pave the way for biotechnological exploitation of unique enzymes from early lineage fungi with potential to contribute to improved biomass conversion. The phyla of ancient fungi through evolution have developed to be very different and together they constitute a rich enzyme discovery pool. Graphical abstract: Image 1 Highlights: Explores the understudied Ancient Fungi: providing novelty and molecular insight. Contributes to resolving Fungal early lineages by interaction secretome studies. Generates conceptually new biological understanding directly from sequencing data. Discovers oxidative LPMO enzymes to be present already in the early lineage fungi. Gives evidence for a common ancestor of fungal plant cell wall degrading enzymes.